Study of interleukin-1 receptor antagonist (IL-1Ra) gene polymorphism in healthy individuals from Northern India - Bid, H. K. (Springer India, 2004)
Cytokines play a key role in immune responses and inflammation. IL-1Ra is a naturally occurring structural variant of IL-1 that competitively inhibits receptor binding of IL-1. We have investigated the polymorphism in intron-2 of the interleukin-1 receptor antagonist gene in North Indian population. This genetic variation has been of great interest due to its possible association with a variety of human diseases primarily of epithelial and endothelial cell origin such as urolithiasis etc. Allele frequencies of the IL-1Ra polymorphism vary among different populations but there is no data till date reported from India. The present study was carried out to determine the IL-1Ra gene Polymorphism in 165 normal unrelated individuals from North India. We obtained an allelic frequency of 63.94, 30.61, 4.55, 0.90 for A, B, C and D allele and percentage of genotypes AA, BB, CC, DD, A/B, A/C, A/D and B/C were 49.7, 18.2, 2.42, 0.60, 24.2, 3.63, 0.60, 0.60 respectively. Our results suggested that the frequency and distribution of this polymorphism in India is substantially different from other populations and ethnic groups.